2007
DOI: 10.1051/0004-6361:20078418
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of Be stars in the direction of the Galactic Bulge

Abstract: Context. Detailed studies of Be stars in environments with different metallicities like the Magellanic Clouds or the Galactic Bulge are necessary to understand the formation and evolution mechanisms of the circumstellar disks. However, a detailed study of Be stars in the direction of the bulge of our own galaxy has not been performed until now. Aims. The aim of this work is to report the first systematic search for Be star candidates in the direction of the Galactic Bulge. We present the full catalogue, give a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Over the past two decades, the microlensing experiments MACHO (Alcock et al 1993), the Optical Gravitational Lensing Experiment II (OGLE-II; Udalski et al 1997), and EROS (Aubourg et al 1995) have provided a database of light curves of a large number of massive stars located in the Magellanic Clouds and the Galaxy, motivating detailed studies of Be stars (Keller et al 2002;Mennickent et al 2002;de Wit et al 2003;Sabogal et al 2005Sabogal et al , 2008 and other types of massive stars. Furthermore, surveys with the All Sky Automated Survey (ASAS ;Pojmanski 2002) and the Hipparcos mission have motivated a couple of studies on variability as a function of spectral type.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the microlensing experiments MACHO (Alcock et al 1993), the Optical Gravitational Lensing Experiment II (OGLE-II; Udalski et al 1997), and EROS (Aubourg et al 1995) have provided a database of light curves of a large number of massive stars located in the Magellanic Clouds and the Galaxy, motivating detailed studies of Be stars (Keller et al 2002;Mennickent et al 2002;de Wit et al 2003;Sabogal et al 2005Sabogal et al , 2008 and other types of massive stars. Furthermore, surveys with the All Sky Automated Survey (ASAS ;Pojmanski 2002) and the Hipparcos mission have motivated a couple of studies on variability as a function of spectral type.…”
Section: Introductionmentioning
confidence: 99%
“…This process conducted us to a catalog of about 29000 BeSC. We found that 198 of these stars exhibit a periodic behavior ( [7]). …”
Section: Techniques Used In Searches For Bescmentioning
confidence: 92%
“…The first comes from OGLE-III and Sabogal et al (2008). We use this data set to train and test our classifiers.…”
Section: Datamentioning
confidence: 99%
“…These variability classes and the number of stars in each class are shown in Table 1. Additionally, we selected the OGLE-III I band light curves of 475 BeSC reported by Sabogal et al (2008) in the direction of the GB, and of 200 BeSC reported by Sabogal et al (2005) in the LMC. These 675 BeSC are included in our training sample since they clearly exhibit the five morphological types shown in Fig.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation